Pengaruh Persepsi Kualitas Layanan dan Persepsi Nilai terhadap Kepuasan dan Loyalitas Pelanggan - Muhammad Fahreza Firdaus; Tetra Hidayati; Saida Zainurossalamia (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
MService Quality and Customer Value Towards Customer Satisfaction and Customer Loyality (Empiricial Studies on Kangoroo Premier Travel Samarinda). Under the gudiance of Tetra Hidayati and Saida Zainurrosallamia The study airned to test wheather Service Quality and Customer Value to Customer Satisfaction and Customer Loyality in Kangoroo Premier Travel Samarinda. Independent variabels in this study is Service Quality and Customer Value. Dependent variabels in this study is Customer Satisfaction and Customer Loyality. This research was conducted on consumers Kangoroo Premier Travel Samarinda consisting of 100 respondents. This type of research is quantitative research. Method of data collection using the questionnaire. Data analysis using Alternatif Structural Modeling. The results showed that Service Quality and Customer Value the positive signficant effect towards Customer Satisfaction and Customer Loyality